Impurity scattering of band carriers - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Mobility of band carriers scattered on donors, partially ionized, partially
neutral, at low temperatures, is considered in general and calculated for AIII-BV group
crystals. It is shown that temperature dependence of mobility is determined by
relationship between number of ionized and neutral donors and by average energy of
electrons.